Analisis Produksi Budidaya Ikan Nila di Kecamatan Kusan Hilir Kabupaten Tanah Bumbu - Nazula, Lilis Sahdatul; Nuryadin, M. Rusmin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research was conducted to find out how business income production and what is the level of tilapia farming business scalein Kusan Hilir District, Tanah Bumbu Regency. By using the Cobb-Douglas model. The respondent of this study were 32 tilapia cultivators. Processing data with analysis revenue and production function analysis using Cobb-Douglas softwere Evies 12. The results of this study indicate tilapia aquaculture business income in Kusan Hilir District, Tanah Bumbu Regency experienced a profit of Rp 79.451.000 with and average profit of Rp 2.482.843. The results of the business scale of tilapia aquaculture production with and elasticity value of 0.802 which means that the value is less than 1 so that the level off business scale tilapia cultivators in Kusan Hilir District, Tanah Bumbu, are at the decreasing return to scale.